Percutaneous repair of Achilles tendon ruptures with Tenolig: Quantitative analysis of postural control and gait pattern - Mezzarobba, S.; Bortolato, S.; Giacomazzi, A.; Fancellu, G.; Marcovich, R.; Valentini, R. (Foot (Edinburgh, Scotland), 2012)
Surgical approach in Achilles tendon's rupture involved during the last years has becoming safer and less invasive as possible. Lots of study investigate the outcomes of the mini-invasive technique with Tenolig proving its good results, but never in the long-term. Our study want to emphasize the effectiveness of this treatment exploring the postural and gait patterns in a 24-month follow up. Patients did self-training exercises without specific supervision, instead of a particular postoperative rehabilitation protocol. We compared 21 patients to a control group of 19 health subjects using a clinical examination, a podobarometric and an optokinetic analysis. Data shows no differences in time-distance parameters, despite a reduction of propulsion phase data, confirmed also by kinetic analysis. Podobarometric results show only a decrease in the anterior pressure of the injured limb (p=0.09). In standing an increase of anterior–posterior oscillation of the COP (center of pressure) (p=0.03). The results underline the long-term outcome effectiveness of the technique but some functional alterations remain. This could be the reason of the weakness, which always affected the patients. Reduction of the triceps elongation and restoration of strength during the propulsion phase should be the key points in postoperative physiotherapy.